The fundamental concept of a crime in international criminal law : a comparative law analysis - Marchuk, Iryna, author (Heidelberg : Springer, 2014)
This book examines the rapid development of the fundamental concept of a crime in international criminal law from a comparative law perspective. In this context, particular thought has been given to the catalyzing impact of the criminal law theory that has developed in major world legal systems upon the crystallization of the substantive part of international criminal law. This study offers a critical overview of international and domestic jurisprudence with regard to the construal of the concept of a crime (actus reus, mens rea, defences, modes of liability) and exposes roots of confusion in international criminal law through a comprehensive comparative analysis of substantive criminal laws in selected legal jurisdictions.
Introduction -- The concept of crime in common law jurisdictions -- The concept of crime in continental law jurisdictions -- The concept of crime in international criminal law -- Evolution of the mens rea doctrine in international criminal law -- Modalities of criminal liability in the jurisprudence of international criminal courts and tribunals -- Grounds excluding criminal responsibility in international criminal law.
Originally presented as the author's thesis (doctoral - Copenhagen) under the title: Reconciliation of major legal systems under the umbrella of international criminal law: a study on the law on Mens rea.
Includes bibliographical references (pages 297-304).
Keywords: International criminal law; Criminal law